Redesain Legal Standing Peninjauan Kembali oleh Jaksa Penuntut Umum Demi Mewujudkan Keadilan Hukum - Ridha, Muhammad (Ridwan Institute, 2021)
The argument for equality before the law in the criminal justice system has not yet contributed to justice to justice seekers. This can be proven in the criminal justice system in Indonesia, where the Public Prosecutor as state attorney who represents the public interest as well as the victim, does not get legal standing, and has no legal standing. law to undertake a legal reconsideration effort. in the course of the criminal justice practice has broken the positivistic legalism which is marked by the emergence of decisions of the Supreme Court which grant the request for reconsideration by the Public Prosecutor. In this case also the decision will be used as a jurisprudence in the future for the same case. Therefore, it is interesting to study and analyze, by formulating two problems, what are the considerations of the Supreme Court in accepting legal remedies for review by the public prosecutor, how to redesign the legal standing of the review by the public prosecutor. This research is a juridical-normative legal research with data collection methods, namely literature study and descriptive-qualitative analysis. The conclusion of this research, the judge in granting the request for reconsideration by the Public Prosecutor, among others, applied the Equality of Arms Principle for a fair trail trial, secondly, revised the Criminal Procedure Code regarding the expansion of the subject of the applicant for legal reconsideration efforts, such as that contained in the Draft Criminal Procedure Code